Pengaruh Return On Equity, Price Earning Ratio, Price To Book Value Dan Inflasi Terhadap Harga Saham PT Bhakti Investama Tbk Jakarta - Pariang Siagian (Bina Nusantara University, 2011)
Investment on stocks is a high-risky investment to make investors to possibly gain a lot of profit. On the other hand, those investors might experience some big loss. Data collecting comes from theoretical books and other related references. Secondary data including Return On Equity (ROE), Price Earnings Ratio (PER), Earning Per Share (EPS), Book Value (BV), Price To Book Value (PBV) and Stock Prices of PT Bhakti Investama Tbk. This research is intended to find whether Return On Equity (ROE), Price Earnings Ratio (PER), Price To Book Value (PBV) and Inflation, have some influences on the Stock Price of PT Bhakti Investama Tbk., both partially and entirely; and how much the influences are.